Influence of two-handed jaw thrust during tracheal intubation on postoperative sore throat: a prospective randomised study. Issue 2 (February 2021) - Huh, Hyub; Go, Doo Yeon; Cho, Jang Eun; Park, Jihoon; Lee, Jiwon; Kim, Hyun-Chang
Objective: General anaesthesia with tracheal intubation results in sore throat. We evaluated the influence of the two-handed jaw thrust on postoperative sore throat in patients who require tracheal intubation. Methods: In this prospective, double-blind, single-centre, parallel-arm, and randomised trial, 92 patients who were scheduled for general anaesthesia for total hip arthroplasty were allocated to one of two groups. In the jaw thrust group (n = 46), the two-handed jaw thrust manoeuvre was applied at intubation. In the control group (n = 46), conventional intubation with sham jaw thrust was performed. Incidences of airway morbidities including sore throat, hoarseness, and cough at 2, 4, and 24 hours postoperatively were compared. Results: During the postoperative 24 hours, the incidence of sore throat (8 [17%] vs. 20 [44%]) and hoarseness were lower in the jaw thrust group (8 [17%] vs. 18 [39%]) compared with the control group. The incidence of cough during the postoperative 24 hours was similar between the groups. Conclusions: The jaw thrust manoeuvre significantly reduced sore throat and hoarseness in patients after general anaesthesia using tracheal intubation. Clinical trial registration: NCT 03568279.